Diversity of trypanosomatids (Kinetoplastea: Trypanosomatidae) parasitizing fleas (Insecta: Siphonaptera) and description of a new genus Blechomonas gen. n - Votýpka, Jan; Suková, Eva; Kraeva, Natalya; Ishemgulova, Aygul; Duží, Ivana; Lukeš, Julius; Yurchenko, Vyacheslav (Protist, 2013)
To further investigate the diversity of Trypanosomatidae we have examined the species present within the flea (Siphonaptera) population in the Czech Republic. Out of 1549 fleas, 239 were found to be infected by trypanosomatids. Axenic cultures were established from 90 infected specimens and 29 of them were further characterized. Molecular phylogenetic analysis of the SL RNA, gGAPDH, and SSU rRNA genes revealed a striking diversity within this group and analyzed isolates were classified into 16 Typing units (TUs) of which 15 typified new species. In addition to one Trypanosoma species, two TUs grouped within the sub-family Leishmaniinae, two clustered together with Herpetomonas, wheras 11 TUs formed a novel clade branching off between Trypanosoma spp. and remaining trypanosomatids. We propose to recognize this clade as a new genus Blechomonas and a new subfamily Blechomonadinae, and provide molecular and morphological description of 11 TUs representing this genus. Our finding of such an ancient host-specific group sheds new light at the origin of Trypanosomatidae and the roots of dixenous parasitism. The strict host restriction of Blechomonas to Siphonaptera with adult fleas' dependence on blood meal may reflect passing of parasites from larvae through pupae to adults and implies potential transmission to the warm-blooded vertebrates.
Keywords: Biodiversity; kDNA; hlodavci; glycosomal glyceraldehyde-3-phosphate dehydrogenase; fylogeneze; gGAPDH; Rodentia; Česká republika; Phylogeny; Blechomonas; kinetoplast DNA; biodiverzita; Trypanosomatidae; molekulární sekvence - údaje; co-evolution.; small subunit ribosomal RNA; Siphonaptera; Czech Republic; typing unit; Trypanosomatina; Animals; zvířata; SSU; host specificity; Molecular Sequence Data; spliced leader RNA gene repeats; phylogeny; TU; SL